Controller design for pilot plant based on transient response criteria / Khairil Anwar Abdul Razak and Suhairi Abdul Ghani - Abdul Razak, Khairil Anwar; Abdul Ghani, Suhairi (1993)
This project was done to obtain the approximate controller settings which are the Proportional, Integral and Derivative (PID) parameters for the various processes based on the FEEDBACK PCS327 Process Control Simulator. The design is based on the transient response criteria of the different processes. Based on this criteria, tuning relations method is used. Field tuning is often required since process models are never exact The tuning relations for PID controllers that were used include the widely-used Ziegler and Nichols method and Cohen and Coon method utilizing the process reaction curve. These different methods were compared to ascertain the most suitable PID control method for the various processes involved.